1996
DOI: 10.1038/383722a0
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional signalling through the EPH-family receptor Nuk and its transmembrane ligands

Abstract: Receptor tyrosine kinases of the EPH class have been implicated in the control of axon guidance and fasciculation, in regulating cell migration, and in defining compartments in the developing embryo. Efficient activation of EPH receptors generally requires that their ligands be anchored to the cell surface, either through a transmembrane (TM) region or a glycosyl phosphatidylinositol (GPI) group. These observations have suggested that EPH receptors can transduce signals initiated by direct cell-cell interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
332
0
1

Year Published

1997
1997
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 500 publications
(340 citation statements)
references
References 25 publications
7
332
0
1
Order By: Relevance
“…Recent ®ndings in other transmembrane growth factor families support this possibility. For example, it was demonstrated that the transmembrane ligands for the EPH-family receptor Nuk had a signaling function (Holland et al, 1996). A Prosite database search of the cytoplasmic tail of wt TGF-a and TGF-a variants revealed a candidate site for prenylation in TGF-a VaI.…”
Section: Discussionmentioning
confidence: 99%
“…Recent ®ndings in other transmembrane growth factor families support this possibility. For example, it was demonstrated that the transmembrane ligands for the EPH-family receptor Nuk had a signaling function (Holland et al, 1996). A Prosite database search of the cytoplasmic tail of wt TGF-a and TGF-a variants revealed a candidate site for prenylation in TGF-a VaI.…”
Section: Discussionmentioning
confidence: 99%
“…Alternative potential functions for the cytoplasmic domains of the transmembrane ligands include cytoskeletal attachment, or transmission of a signal into the interior of the ligand-presenting cell . In relation to all these potential functions, it is interesting that recent studies have indicated receptor binding results in phosphorylation of the transmembrane ligands ephrin-B1 and (Bruckner et al, 1997;Holland et al, 1996). It is not yet known what the biological function of such transmembrane signaling through the ligand may be, though genetic evidence suggests the possibility that the ephrin-B ligands might transduce an axon guidance signal into the cell that carries them Orioli et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The ephrin-B ligands are anchored by a transmembrane domain and in addition to ephrin-B3, described here, include two other ligands, ephrin-B1 (originally named LERK-2/Elk-L/Cek5-L) (Beckmann et al, 1994;Davis et al, 1994;Shao et al, 1994) and ephrin-B2 (originally named ELF-2/Htk-L) (Bennett et al, 1995;Bergemann et al, 1995). Recent evidence indicates that receptorligand binding can result in phosphorylation of the transmembrane ligands, indicating bi-directional signal transduction through both the receptor and the ligand (Bruckner et al, 1997;Holland et al, 1996).…”
Section: Introductionmentioning
confidence: 90%
“…In the mouse, a simple two-segment periodicity of receptor and ligand expression has been described, with an Eph receptor, EphA4, being a target of krox-20 in r3 and r5, and a ligand, ephrin-B2, being expressed in r2, 4, and 6 (Flenniken et al, 1996;Theil et al, 1998). Importantly, signalling between these classes of Eph and ephrin is cell-contact dependent and bidirectional, with downstream signalling being activated in both ligand and receptor expressing cells (Holland et al, 1996;Bruckner et al, 1997). In the embryo shown in Figure 9A, activation of EphA4 signalling in the misplaced krox-20-expressing cells in r2, and activation of ephrin signalling in the cells immediately surrounding them is hypothesized to cause those cells to move until they are safely within r3, amongst other ephA4-expressing cells and away from the influence of ephrinB2-expressing cells.…”
Section: Repulsive Interactions Between Ephs and Ephrins Mediate Cellmentioning
confidence: 99%